Cardio-pulmonary resuscitation challenges in selected Botswana hospitals: Nurse managers' views - Lakshmi Rajeswaran; Valerie J. Ehlers (AOSIS, 2013)
Road traffic accident victims, as well as persons experiencing cardiac and other medical emergencies, might lose their lives due to the non-availability of trained personnel to provide effective cardio-pulmonary resuscitation (CPR) with functional equipment and adequate resources. The objectives of the study were to identify unit managers' perceptions about challenges encountered when performing CPR interventions in the two referral public hospitals in Botswana. These results could be used to recommend more effective CPR strategies for Botswana's hospitals. Interviews, comprising two quantitative sections with closed ended questions and one qualitative section with semi-structured questions, were conducted with 22 unit managers. The quantitative data indicated that all unit managers had at least eight years' nursing experience, and could identify CPR shortcomings in their hospitals. Only one interviewee had never performed CPR. The qualitative data analysis revealed that the hospital units sometimes had too few staff members and did not have fully equipped emergency trolleys and/or equipment. No CPR teams and no CPR policies and guidelines existed. Nurses and doctors reportedly lacked CPR knowledge and skills. No debriefing services were provided after CPR encounters. The participating hospitals should address the following challenges that might affect CPR outcomes: shortages of staff, overpopulation of hospital units, shortcomings of the emergency trolleys and CPR equipment, absence of CPR policies and guidelines, absence of CPR teams, limited CPR competencies of doctors and nurses and the lack of debriefing sessions after CPR attempts. Die slagoffers van padongelukke, asook persone wat hart- en ander mediese noodtoestande ervaar, kan hulle lewens verloor omdat daar nie opgeleide personeel met funksionele toerusting en voldoende hulpbronne beskikbaar is om effektiewe kardiopulmonale resussitasie (KPR) te doen nie. Die studie het ten doel gehad om eenheidsbestuurders se persepsies te bepaal oor uitdagings wat hulle in die gesig staan wanneer KPR-tussentredes plaasvind in die twee openbare hospitale in Botswana wat as verwysingshospitale dien. Die bevindings kan gebruik word om effektiewer KPR-strategieë vir Botswana se hospitale aan te beveel. Onderhoude bestaande uit twee kwantitatiewe afdelings met geslote vrae en een kwalitatiewe afdeling met semi-gestruktureerde vrae is met 22 eenheidsbestuurders gevoer. Die kwantitatiewe data het aangedui dat alle eenheidsbestuurders minstens agt jaar se verpleegervaring het en dat hulle die tekortkomings sover dit KPR in hulle hospitale aangaan, kon identifiseer. Slegs een persoon het nog nooit KPR toegepas nie. Die ontleding van die kwalitatiewe data dui daarop dat hospitaaleenhede soms te min personeel het en dat hulle nie ten volle toegeruste noodtrollies en/of toerusting het nie. Geen KPR-spanne en geen KPR-beleid of -riglyne bestaan nie. Verpleegkundiges en dokters het volgens die onderhoude 'n gebrek aan KPR-kennis en -vaardighede. Geen ontlontingsdienste is na KPR-voorvalle vir die personeel beskikbaar nie. Die deelnemende hospitale behoort die uitdagings aan te spreek wat KPR-uitkomste kan beinvloed. Hierdie uitdagings sluit in personeeltekorte, oorbesetting in hospitaaleenhede, tekortkomings in die noodtrollies en toerusting, die gebrek aan KPR-beleid en -riglyne, die afwesigheid van KPR-spanne, dokters en verpleegsters se beperkte KPR-vaardighede en die feit dat ontlontingsdienste nie na KPR-pogings vir personeellede beskikbaar is nie.